Potential Test of Jungle Water Guava (Zysigium jambos (L). Alston) Timor as Immunomodulator against Antibody Response of Broiler Chicken (Gallus domesticus) In Vivo - Susar, Imelda; Seran, Lukas; Nau, Wilhelmina Getrudis (Program Studi Pendidikan Biologi, 2024)
The study aims to determine the potential of Syzigium jambos (L.) Alston) Timor extract as an immunomodulator against the antibody response of broiler chickens (Gallus domesticus) in vivo. To determine what is the difference in immunomodulation between concentration levels of Syzigium jambos (L.) Alston ) Timor extract on the antibody response of broiler chickens (Gallus domesticus) in vivo. To determine whether there is a difference in immunomodulating ability of Syzigium jambos (L.) Alston ) Timor extract between the negative control group, experimental group and positive control group. Methods of the study used a research design with three treatment units, namely negative control, extract treatment and positive control following the pre-test post-test control group design. Data were analyzed descriptively and inferentially. The conclusion of this study is 1) Timor forest water guava bark extract is proven to have the potential as an immunomodulator against the antibody response of broiler chickens (Gallus domesticus) in vivo. 2) There are differences in immunomodulation between concentration levels of Timor forest water guava bark extract on the antibody response of broiler chickens (Gallus domesticus) in vivo, especially at a concentration of 25% with an average antibody titer of 853.3 cells/µl blood, while at concentrations of 50% and 75% there is no difference with an average antibody titer of 1024 cells/µl blood. 3) There is a difference in immunomodulation ability between the forest water guava bark extract (Zysigium jambos (L.) Alston) Timor group and the negative control group, but